(untitled) (World Science, 2020)
Throughout the history of music, the dialogue of cultures in the West- East discourse has produced various Orientalism models. Introducing a fashion for oriental decorations in Europe, using new instruments, borrowing modes of musical expression, as well as alluding to signs and symbols of oriental religions and philosophies gave rise to reshaping European musical aesthetics as early as the 18th century. At that time, Wolfgang Amadeus Mozart and his work were undoubtedly pivotal for the art. One can retrospectively observe that Turkish Janissary musical traditions significantly freshened and enriched the composer’s instrumental thinking. This can be seen most in the orchestration of Mozart’s oriental operas – namely, his singspiels Zaide and The Abduction from the Seraglio. Being a synthetic genre by its nature, opera is primarily related to literary activity; therefore, its oriental colour and imagery need to be immersed in the philosophical world of oriental narratives and storylines that were very popular in baroque and classicism art. Moreover, on the example of The Magic Flute, Mozart’s last opera, we can observe how the semiosis of Sufi texts explicitly present in this singspiel libretto gives the work new – Romantic – features. These new characteristics are not limited to the surface aesthetic level of decorations. As an opera reformer, Mozart reshapes the aesthetics of musical language, concurrently refining the ethical component of the genre. Thus, when analysing some instrumental, especially opera pieces by Mozart – namely, Zaide, The Abduction from the Seraglio and The Magic Flute singspiels, one can affirm that the synergy between all orientalism features in the composer’s works and established traditions of the European musical art resulted in the Viennese master creating a new ethical and aesthetic style model, which became seminal for the upcoming epochs.